AB0600 Alfacalcidol (D-hormone analog) modulate inflammatory cytokine production without conversion to calcitriol. (23rd January 2014) - Vojinovic, J.; Zivanovic-Radnic, T.; Sefik-Bukilica, M.; Simic-Pasalic, K.; Damjanov, N.
Abstract : Background: D hormone 1, 25(OH)2D3 (calcitriol) is believed to be the only active form of D hormone (synthesized from vitamin D - cholecalciferol) within the body. It is well known that high doses of D hormone exert immunomodulatory properties that could benefit rheumatoid arthritis [1]. Alfacalcidol, synthetic D hormone analogue 1(OH)D3, compared to calcitriol, is known for its safer profile (lower hypercalcemic activity) when used in higher doses. Mostly it is used for prophylaxis and treatment of osteoporosis, but some encouraging results were achieved in rheumatoid arthritis as well [2]. Actually it is believed that alfacalcidol must be hydroxylated at 25 position (conversion to calcitriol) to induce any effect on cells. Objectives: Aim of the study was to investigate if alfacalcidol itself could influence cytokine production, as calcitriol does, shifting Th1 to Th2 profile. Methods: Isolated peripheral blood mononuclear cells (PBMC), from 20 healthy volunteers, were stimulated with PMA and Ionomycin and cultivated in cell cultures (48 hours at 37°C, 5% CO2 ) medium without supplements or supplemented with 10 nM of alfacalcidol or calcitriol, respectively. Produced levels of IL-17A, IL-21, IL-23, IFN-γ, TNF-α, and IL-4 were measured in cell culture supernatant by standard manufacturer ELISA method. Results: In vitro test results have shown that alfacalcidol can act on cells directly, and there was no statistically significant difference compared to calcitriol. Compared to controls, without any supplements in culture, alfacalcidol and calcitriol significantly reduced production of IL-17 (p<0.001), IL-21 (p<0.001) and TNF-α (p<0.05) while increased production of IL-4 (p<0.001) and IFN-γ (p<0.05). Production of IL-23 was not influenced by both types of D- hormone. Conclusions: This is the first prove that alfacalcidol, as a synthetic vitamin D analogue, may act on cells directly, without 25-hydroxylation to calcitriol. Same as calcitriol, it has immunomodulatory potential, promoting Th2 while inhibiting Th1-cytokine profile. Better safety profile when used in high doses and ability to suppress Th17 production in activated cells could provide considerable therapeutic potential on lymphocyte differentiation and osteoclasts benefiting RA and secondary osteoporosis. References: Cutolo M. Vitamin D and autoimmune rheumatic diseases. Arthritis Research & Therapy 2008; 10:123-4 Andjelkovic Z, Vojinovic J, Pejnovic N et al. Disease modifynig and immunoregulatory effects of high oral dose 1a(OH)D3 in rheumatoid arthritis patients. Clin Exp Rheumatol 1999; 17(4): 59-62. Disclosure of Interest: None Declared